Innovations in Food Production - Status and Directions of Development - Grzybowska, Barbara (Olsztyn Economic Journal, 2012)
This paper characterises the directions of innovative activities undertaken by food industry enterprises concerning the manufacturing of food products. Based on the subject literature and secondary statistical data, the status of food industry innovativeness and areas of innovative activities related to implementation of technological and non-technological innovations are presented. The activities of enterprises focus on manufacturing new products in response to the ever-changing needs and expectations of consumers. In particular, the production of so-called functional food (which seeks to promote health, minimise the risk of specific diseases, improve psychophysical fitness, lose weight, etc.) is increasingly extensive. Manufacturers must also improve the technologies and techniques of product manufacturing, packaging and storage.